2013
DOI: 10.1007/s10393-013-0884-9
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Foodborne Bacterial and Parasitic Zoonoses in Vietnam

Abstract: Vietnam has experienced unprecedented economic and social development in recent years, and the livestock sector is undergoing significant transformations. Although food animal production is still dominated by small-scale ‘backyard’ enterprises with mixed crop–livestock or livestock–aquatic systems, there is a trend towards more intensive and vertically integrated operations. Changes in animal production, processing and distribution networks for meat and animal products, and the shift from wet markets to superm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 114 publications
1
48
0
6
Order By: Relevance
“…Zoonotic and foodborne pathogens have been identified in pig production facilities in Vietnam, and the prevalence of such pathogens may be greater in smallholder pig farms (Tran et al 2004, Carrique-Mas et al 2014. Eating raw or undercooked pig products in traditional dishes, which occurs in Southeast Asian countries including Vietnam (Ho et al 2011, Huong et al 2014, increases potential for spread of zoonotic pathogens from pigs to humans (Wertheim et al 2009, Carrique-Mas and Bryant 2013, Huong et al 2014. Twenty-two percent of patients in our study reported this behaviour, similar to results of a previous study in Hanoi Province which reported that an average of 21% of rural and urban individuals ate raw pig products as a part of traditional dishes (Huong et al 2014).…”
Section: Discussionsupporting
confidence: 85%
“…Zoonotic and foodborne pathogens have been identified in pig production facilities in Vietnam, and the prevalence of such pathogens may be greater in smallholder pig farms (Tran et al 2004, Carrique-Mas et al 2014. Eating raw or undercooked pig products in traditional dishes, which occurs in Southeast Asian countries including Vietnam (Ho et al 2011, Huong et al 2014, increases potential for spread of zoonotic pathogens from pigs to humans (Wertheim et al 2009, Carrique-Mas and Bryant 2013, Huong et al 2014. Twenty-two percent of patients in our study reported this behaviour, similar to results of a previous study in Hanoi Province which reported that an average of 21% of rural and urban individuals ate raw pig products as a part of traditional dishes (Huong et al 2014).…”
Section: Discussionsupporting
confidence: 85%
“…This is likely to reflect existing research capacity as well as public health priorities. NTS is considered one of the most common foodborne bacterial pathogens in the region [113,114]. In addition, the spread of NTS has been linked to international travel and global food trade [115].…”
Section: Discussionmentioning
confidence: 99%
“…For example, consuming raw vegetables such as kangkong-kalabau ( Enhydra fluctuants ) and Brahmi ( Herpestis monniera ) contaminated with metacercariae of Fasciola spp., or eating raw/pickled pork (nem chua and nem chao), vegetables and dog meat contaminated with taeniid eggs and cysts of T. solium [12, 13]. Besides, proximity with infected livestock, use of human faeces as fertilizer, poor sanitation and others, further increase disease transmission to humans [5, 14, 15]. …”
Section: Discussionmentioning
confidence: 99%